Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
pq+qr+pr= pqr (because they are both equal to -1)
then you divide both sides by p to get
q+ qr/p + r = qr. then you divide both sides by q and get
r/p + r/q = r. so I divided both sides by r to get
P + q =0 therefore p= -q. putting that into the first equation allows you to get that r=1 because p and q cancel each other out. then I put that into pq+qr+pr=-1 so pq+q+p=-1 since p=-q the q+p gets canceled out and you're left with pq=-1 and since it is the product of the two numbers and q is the negative of p. q=-1 while p=1. therefore p=1 r=1 and q=-1
then you divide both sides by p to get
q+ qr/p + r = qr. then you divide both sides by q and get
r/p + r/q = r. so I divided both sides by r to get
P + q =0 therefore p= -q. putting that into the first equation allows you to get that r=1 because p and q cancel each other out. then I put that into pq+qr+pr=-1 so pq+q+p=-1 since p=-q the q+p gets canceled out and you're left with pq=-1 and since it is the product of the two numbers and q is the negative of p. q=-1 while p=1. therefore p=1 r=1 and q=-1
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.